THE IMPLEMENTATION OF NEW NORMAL POLICIES DURING THE COVID-19 PANDEMIC IN KENDARI CITY, SOUTHEAST SULAWESI, INDONESIA: KNOWLEDGE, ATTITUDES AND PRACTICE - Saimin, Juminten; Purnamasari, Nur Indah; Hartati, Hartati (YCAB Publisher & IAKMI SULTRA, 2020)
Background: The new normal policy during the COVID-19 pandemic requires public participation. Efforts to suppress the number of cases require knowledge, attitudes and behavior towards health protocols to prevent COVID-19.Objective: This study aimed to assess knowledge, attitudes and practice towards the prevention of COVID-19.Method: This was a descriptive study which included 409 respondents in Kendari City Indonesia conducted in July-August 2020. Data were collected through online questionnaires with google forms.Results: Most of the respondents knew the causes of COVID-19 (85.1%), mode of transmission (65.0%), prevention with masks (96.4%), washing hands (90.5%), social distancing (98.1%), and cough etiquette (80.4%). The attitudes towards public opinions varied. The behaviors towards the prevention of COVID-19 were reading (90.2%), protecting themselves (94.4%), positive thinking (96.1%), doing activities at home (87.3%) and social distancing (93.2%). The behavior to avoid fake news was to ensure the news sources (72.6%), accessed official news (85.5%) and accessed many sources (73.8%).Conclusions: The community of Kendari City has adequate knowledge, attitudes and practice towards prevention of COVID-19. This is a potential asset to implementing the new normal policy during the COVID-19 pandemic.